Internalizing and externalizing problems and how they relate to academic self-concept in students at Gateway High School - Nyathi, Christopher (Midlands State University, 2017)
The relationship between internalizing and externalizing problems and Academic Self-concept in high school students is unsettled. The purpose of the current study was to examine the internalizing and externalizing problems and how they relate to Academic Self-Concept. Internalizing and externalizing problems are indicators of poor mental health in high school students and a public health concern. The study employed a quantitative research approach and a descriptive survey research design. Participants included 160, high school students from 13 – 17 years who were selected using a purposive sampling technique. The sample size was determined using the sample size calculator software package. Data was analyzed using the SPSS software package and Pearson correlation was used. 9.5% of the participants were found to have severe internalizing problems, whilst 10% were found to have severe externalizing problems. Of the students, 3.4% were reported to have a low Academic Self-Concept. The relationship between externalizing problems and Academic Self-Concept was found to be r= -0.447 and a r= -0.510 was found to exist between internalizing problems and Academic Self-Concept. 22.5% of the students had a negative impact score whereas, 19.2% of the students scored a high total difficulties score on the Strengths and Difficulties Questionnaire. Students at Gateway High School mostly experience peer problems in regards to internalizing problems and conduct problems when it comes to externalizing problems. There is a strong association that exists between internalizing and externalizing problems and Academic Self-Concept.